胚胎移植新进展 Advances in Embryo Transfer - Wu, Bin (IntechOpen, 2014)
本书阐述了生殖医学相关的技术知识，以21世纪最新进展和发展趋势为重点，注重创新性、实用性。 其内容从最佳的卵巢刺激方案、授精技术新进展，到胚胎移植操作技巧、胚胎冷冻保存以及子宫内膜容受性的最新研究成果等都做了详尽的描 述。本书旨在帮助更多从事辅助生殖技术的人员了解本领域最新进展，更新此领域中科学研究和临床诊治观念，以提高诊疗水平达到最佳活产 率。Embryo transfer has become one of the prominent high businesses worldwide. This book updates and reviews some new developed theories and technologies in the human embryo transfer and mainly focus on discussing some encountered problems during embryo transfer, which gives some examples how to improve pregnancy rate by innovated techniques so that readers, especially embryologists and physicians for human IVF programs, may acquire some new and usable information as well as some key practice techniques. Major contents include the optimal stimulation scheme for ovaries, advance in insemination technology, improved embryo transfer technology and endometrial receptivity and embryo implantation mechanism. Thus, this book will greatly add new information for readers to improve human embryo transfer pregnancy rate.Please note that this is the official Chinese translation of the book originally published in English.